Biomedical applications of organoids derived from the digestive system - Xu, Zhensheng; Lei, Zhongwen; Cheng, Qiuhua; Gao, Yuanhui; Xiang, Yang (Frontiers in Cell and Developmental Biology, 2025)
The global incidence of digestive system diseases is increasing, posing a significant public health challenge and driving an escalating demand for research into the mechanisms underlying their onset and progression. Traditional cell models and xenotransplantation animal models have been widely used to simulate human digestive diseases, thereby enhancing our understanding of disease occurrence, progression, and drug resistance. However, these models fail to fully replicate the complex cellular microenvironment and spatial structure, and are further limited by individual and species differences. Organoid technology, as an emerging in vitro cell culture approach, enables the precise culturing and differentiation of human stem cells to generate highly tissue-specific and functionally intact organoids. This technology not only better recapitulates cell-to-cell interactions, extracellular matrix (ECM) microenvironment, and organ-specific physiological functions but also more closely mimics the human physiological state in vitro. Moreover, it reduces reliance on animal experiments, enhances the translatability of research findings, mitigates the limitations of animal models and two-dimensional cell models, and plays a pivotal role in simulating the physiological and pathological processes of the human digestive tract. Currently, common techniques for constructing organoids include embedding culture, rotating culture, magnetic suspension culture, organ-on-a-chip, three-dimensional (3D), and four-dimensional (4D) printing technologies. Seed cells are primarily derived from digestive system epithelial cells and pluripotent stem cells. This article reviews the construction methods of digestive system organoids, evaluates their applications in studying growth and development mechanisms, disease modeling and mechanism research, drug screening, regenerative medicine, and precision medicine, and identifies existing challenges and future research directions to provide a valuable reference for biomedical research.